2021
DOI: 10.1088/1755-1315/723/2/022105
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the development of grafted grape seedlings on a nursery garden of different graft-rootstock combinations

Abstract: In 2019-2020, experiments were laid on the fields of the ARRIV&W – Branch of FRARC with the aim of experimentally determining the phenotypic signs of compatibility of scion-rootstock combinations with the participation of grape varieties of interspecific origin Denisovskiy and Prestige and rootstock varieties Kober 5 BB and Riparia Rupestris 101-14 introduced to the State Register of Breeding Achievements of the Russian Federation, approved for use. According to the results of the studies, it can be conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For example, Wang et al (2019) revealed that 5A, Harmony, and Riparia Gloire enhanced the flavonol concentrations of Cabernet Sauvignon grapes, while SO4 slightly decreased most of the individual anthocyanin concentrations. A study reported that the Alicante Bouschet/1103P graft combination contained higher concentrations of total phenols and nonflavonoids, total monomeric anthocyanins, and monomeric and polymeric tannins in the seeds than own-rooted or other graft combinations ( Titova et al, 2021 ). Nedelkovski et al (2017) found a higher level of total phenols in the berries of Vranec grafted on Teleki rootstock, 41B could increase total anthocyanins concentrations in the berries, and Fercal could increase total flavan-3-ols concentrations in the berries.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wang et al (2019) revealed that 5A, Harmony, and Riparia Gloire enhanced the flavonol concentrations of Cabernet Sauvignon grapes, while SO4 slightly decreased most of the individual anthocyanin concentrations. A study reported that the Alicante Bouschet/1103P graft combination contained higher concentrations of total phenols and nonflavonoids, total monomeric anthocyanins, and monomeric and polymeric tannins in the seeds than own-rooted or other graft combinations ( Titova et al, 2021 ). Nedelkovski et al (2017) found a higher level of total phenols in the berries of Vranec grafted on Teleki rootstock, 41B could increase total anthocyanins concentrations in the berries, and Fercal could increase total flavan-3-ols concentrations in the berries.…”
Section: Introductionmentioning
confidence: 99%
“…Although, raw materials (i.e. rootstock) are determinants of grape production (Titova et al, 2021) but the fulfillment of such raw materials is not the main desire. This is because the community has already met these raw materials independently.…”
Section: Farmers' Perceptions and Expectations Of Jobs In The Agricul...mentioning
confidence: 99%